Discordance Between Clinical and Pathological Staging and Grading in Upper Tract Urothelial Carcinoma - Mori, Keiichiro; Katayama, Satoshi; Laukhtina, Ekaterina; Schuettfort, Victor M; Pradere, Benjamin; Quhal, Fahad; Sari Motlagh, Reza; Mostafaei, Hadi; Grossmann, Nico C; Rajwa, Pawel; Zimmermann, Kristin; Karakiewicz, Pierre I; et al. (Clinical genitourinary cancer, 2022)
INTRODUCTION: This study aimed to evaluate the concordance in tumor stage and grade between ureteroscopic (URS) biopsy and radical nephroureterectomy (RNU) in patients with upper tract urothelial carcinoma (UTUC). PATIENTS AND METHODS: Records of 1,214 UTUC patients who had undergone URS biopsy followed by RNU were included. Univariable and multivariable logistic regression analyses were performed to identify factors contributing to the pathological upstaging. RESULTS: The concordance between URS biopsy-based clinical and RNU pathological staging was 34.5%. Clinical understaging occurred in 59.5% patients. Upstaging to muscle-invasive disease occurred in 240 (41.7%) of 575 patients diagnosed with ≤cT1 disease. Of those diagnosed with muscle-invasive disease on final pathology, 89.6% had been clinically diagnosed with ≤cT1 disease. In the univariable analyses, computed tomography urography (CTU)-based invasion, ureter location, hydronephrosis, high-grade cytology, high-grade biopsy, sessile architecture, age, and women sex were significantly associated with pathological upstaging (P < .05). In the multivariable analyses, CTU-based invasion and hydronephrosis remained associated with pathological upstaging (P < .05). URS biopsy-based clinical and pathological gradings were concordant in 634 (54.2%) patients. Clinical undergrading occurred in 496 (42.4%) patients. CONCLUSIONS: Clinical understaging/undergrading and upstaging to muscle-invasive disease occurred in a high proportion of UTUC patients undergoing RNU. Despite the inherent selection bias, these data underline the challenges of accurate UTUC staging and grading. In daily clinical practice, URS biopsy and CTU offer the most accurate preoperative information albeit with limited predictive value when used alone. These findings should be considered when utilizing preoperative, risk-adapted strategies.
Keywords: hydronefróza; Biopsy; Humans; Radical nephroureterectomy; karcinom z přechodných buněk; Computed tomography urography; ureteroskopie; Female; Grade; Upper tract urothelial carcinoma; lidé; Ureteroscopy; ženské pohlaví; Ureteral Neoplasms; Male; nádory močového měchýře; Retrospective Studies; Hydronephrosis; Carcinoma, Transitional Cell; retrospektivní studie; nádory močovodu; mužské pohlaví; Urinary Bladder Neoplasms; Stage